Conflicting social norms and white children’s expressions of intergroup racial attitudes: a socio-normative developmental model - Rodrigues, Ricardo Filipe Pinto Borges (2015)
This thesis examines, in four quasi-experimental studies (N = 663), 6 to 10 years-old White Portuguese children’s expressions of intergroup racial attitudes, with the aim of testing a Socio-Normative Developmental Model (NDM). The NDM holds that the expression of racial attitudes in childhood constitutes an outcome of children’s acknowledgment and situational-salience of two conflicting social norms, namely an anti-racism norm which prohibits the discrimination against the Blacks, and an in-group-loyalty norm which supports in-group favouring behaviour. More specifically, the NDM predicts that children’s expression of racial bias reflects children’s acknowledgment and salience of an in-group-loyalty norm, while the inhibition of racial bias reflects children’s acknowledgment and salience of an antiracism norm. In support of this hypothesis, the results showed that an age-related decrease in the expression of racial bias under a condition of in-group-accountability was associated to acknowledgment and influence of in-group-loyalty norm for younger children (6 years-old) and acknowledgment and influence of an anti-racism norm for older children (9/10 years-old). As to children’s expression of racial attitudes under a condition of non-accountability, the results revealed age-constant levels of racial bias, associated to the internalization of the ingroup- loyalty norm in the case of 9/10 years-old. All in all, these findings state the importance of examining the processes and dynamics of conflicting group norms in order to understand the modifications in children’s expression and inhibition of racial bias that take place between contexts and in the course of childhood.